Profiting with Iron Condor Options : Strategies from the Frontline for Trading in Up or Down Markets - Benklifa, Michael (Pearson Business, 2011)
In a straightforward approach, Hanania Benklifa provides readers the practical knowledge needed to trade options conservatively in Profiting with Iron Condor Options: Strategies from the Frontline for Trading in Up or Down Markets. The objectives are simple: make 2%-4% a month staying in the market as little as possible. Market experts use option condors to consistently earn monthly returns while trading conservatively and staying in the market as little as possible. Benklifa--who manages $10+ million in condor trades each month--shows you exactly how to run these trades and earn these returns, delivering all the details you need to master every nuance of this remarkable strategy. Benklifa shares option condors examples using market realities, not oversimplified abstractions. You'll learn how to handle real-life market dynamics that can dramatically impact results, including rising and falling volatility, changing bid-ask spreads, and distorted call parity. You'll learn how to profit in the sideways markets where condor options are most widely used--and also in extreme-trending markets that offer their own surprising opportunities. Traders who focus on a specific type of trade have a history of outperforming stock pickers and directional investors. This book will give you that deep and usable level of knowledge about one of today's most well-proven strategies:option condors.